Heart rate variability in patients being treated for dengue viral infection: new insights from mathematical correction of heart rate - CARTER III, ROBERT; Hinojosa-Laborde, Carmen; Convertino, Victor A. (Frontiers in Physiology, 2014)
Introduction: Severe dengue hemorrhagic fever (DHF) is a viral infection that acts to increase permeability of capillaries, resulting in internal hemorrhage. Linear frequency domain Fourier spectral analysis represents the most published noninvasive tool for diagnosing and assessing health status via calculated heart rate variability (HRV). As such, HRV may be useful in assessing clinical status in DHF patients, but is prone to erroneous results and conclusions due to the influence of the average HR during the time period of HRV assessment (defined as the ’prevailing’ HR). We tested the hypothesis that alterations in HRV calculated with linear frequency analysis would be minimal when mathematically corrected for prevailing HR following dengue viral infection. Methods: Male (N=16) and female (N= 11) patients between the ages of 6 months and 15 years of age (10 ± 6 SD years) were tracked through the progression of the dengue viral infection with treatment following the abatement of a fever (defervescence). Electrocardiographic recordings were collected and analyzed for HRV. Results: High frequency (HF), low frequency (LF), and LF/HF ratio were unaffected by correction for prevailing HR. Conclusion: HRV corrected for changes in HR did not alter the interpretations of our data. Therefore, we conclude that cardiac parasympathetic activity (HF frequency) is responsible for the majority of the HR reduction following defervescence in patients with dengue viral infection.